(untitled) (Universal International Scientific Journal, 2026)
In this article, the mechanism of recombination processes in α-Si:H films is studied using the method temperature dependence Steady-State Photoconductivity. Using solutions of the continuity and electroneutrality equations, it is shown that the nonmonotonicity in the σ σ0(1/T) coupling obtained for heavily doped α-Si:H films arises from the different occurrence of recombination processes in D-centers in different temperature ranges.